2015
DOI: 10.1039/c5ra12308a
|View full text |Cite
|
Sign up to set email alerts
|

Azide–acetonitrile “click” reaction triggered by Cs2CO3: the atom-economic, high-yielding synthesis of 5-amino-1,2,3-triazoles

Abstract: A Cs 2 CO 3 -catalyzed azide-acetonitrile [3+2]-cycloaddition reaction of monosubstituted acetonitriles with aryl azides has been developed for the synthesis of 5-amino-1,2,3-triazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…Three sets of reagents that have been previously reported to facilitate such cyclizations were screened: stoichiometric sodium methoxide (Alfred, 1970; L’abbé and and Beenaerts, 1989; Julino and Stevens, 1998), stoichiometric sodium ethoxide (Hoover and Day, 1956; Livi et al, 1979), and catalytic cesium carbonate (Krishna et al, 2015). In most cases the choice of base between stoichiometric sodium ethoxide and catalytic cesium carbonate had little to no impact on the yield (e.g., 1 , Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Three sets of reagents that have been previously reported to facilitate such cyclizations were screened: stoichiometric sodium methoxide (Alfred, 1970; L’abbé and and Beenaerts, 1989; Julino and Stevens, 1998), stoichiometric sodium ethoxide (Hoover and Day, 1956; Livi et al, 1979), and catalytic cesium carbonate (Krishna et al, 2015). In most cases the choice of base between stoichiometric sodium ethoxide and catalytic cesium carbonate had little to no impact on the yield (e.g., 1 , Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, carbon‐nitrogen triple‐bonds based click polymerization is another attracting research direction because the organic reactions have been reported. For example, the azide‐acetonitrile click reaction was reported and 5‐amino‐1,2,3‐triazoles could be generated . In addition, a new highly efficient silver catalyzed click reaction of terminal alkynes and isocyanides was presented in the literature .…”
Section: Perspectives Of Click Polymerizationmentioning
confidence: 99%
“…Biologically active 1,2,3‐triazoles primarily include 1,4‐disubstituted 5‐amino 1,2,3‐triazoles [10] and 5‐alkyl(aryl)amino derivatives of 1,2,3‐triazole [11] . The presence of an amino group at position 5 is often responsible for the manifestation of the maximum biological activity [6,12] .…”
Section: Introductionmentioning
confidence: 99%